A Hundred Years of Han (vol.2) : Being the Chronicle of the Later Han Dynasty for the Years 57 to 156 AD as Recorded in Chapters 44 to 53 of the Zizhi tongjian of Sima Guang - Crespigny, Rafe de, (Asian Studies E-Books Online, Collection 2025., 2025)
This is Volume 2 of a 2-volume set: Compiled by the scholar statesman Sima Guang of the Song dynasty, Zizhi tongjian is well recognised as one of the major histories of China. In length and extent, Later or Eastern Han was one of the great empires of east Asia, and its eventual failure led to the heroic age of the Three Kingdoms and centuries of division between north and south. Sima Guang's account of the dynasty's successes and failures provides detailed and informed information on the nature and governance of the Chinese imperial state. This translation offers a Western reader access to and an understanding of that world.